Wsparcie społeczne a kontrola poziomu cukru we krwi w cukrzycy typu 2 - Kocemba, Iwona (Acta Universitatis Lodziensis. Folia Psychologica, 2007)
Diabetes is an incurable disease. Recently researchers are focusing more often on the role of the social support in diabetes treatment. It seams that support from family and friends plays a big role in the results of the disease treatment. Lack of such support may decrease patients’ treatment motivations. The aim of this study was to estimate the relationship between social support and metabolic control. The group which was examined consisted of 35 people with type 2 diabetes not treated with insulin and 31 who were on insulin. The Social Support Inventory by Saranson and glycosylated hemoglobin (HbA1c) for glycemic control were used in this study. The research indicates that poorer metabolic control was correlated with the lack of social support.